Lipid metabolism, antioxidant status and meat sensorial profile in pigs supplemented with plant extracts (Origanum vulgare L. and/or Rosmarinus officinalis) - Beghelli, Daniela; Bailetti, Lucia; Cavalluci, Clarita; Ferraro, Stefano; Olivi, Lucia; Polidori, Paolo (Progress in Nutrition, 2014)
In this study the effect of diets supplemented with extracts of oregano and/or rosemary (Origanum vulgare L. and/or Rosmarinus officinalis L.) on lipid metabolism, antioxidant status and sensory perceptions in meat was investigated in fattening pig. Eighty pigs were divided into five dietary groups (n.16/each identified as: control, C; 2: foil, F; 3: foil + 0.2% oregano, O; 4: foil + 0, 2% rosemary, R and 5: foil + 0.1% + 0.1% oregano, rosemary, OR). Blood samples were drawn from jugular vein after about 15 days of adaptation to the new diet and at the end of the finishing period (160 kg) Samples were used to determine the concentrations of cholesterol, triglycerides, β-hydroxy-butyrate, free fatty acids, the total antioxidant power and reactive metabolites oxygen. Sensory analysis was carried out on meat samples with the test ‘Duo-Trio Test’ and Ordering test on the basis of Preference (ISO 8587:2006). Integration with phyto derivates did not result in significant changes in the blood parameters investigated, while from the point of view of sensory analysis, the presence of oregano was somehow ‘felt’ so that the group of pigs supplemented with oregano have always been recognized as different from the control in terms of texture and flavor.